Early Breast Cancers During Pregnancy Treated With Breast-Conserving Surgery in the First Trimester of Gestation: A Feasibility Study - Blundo, Concetta; Giroda, Massimo; Fusco, Nicola; Sajjadi, Elham; Venetis, Konstantinos; Leonardi, M. Cristina; Vicini, Elisa; Despini, Luca; Rossi, Claudia F.; Runza, Letterio; Sfondrini, Maria S.; Piciotti, Roberto; et al. (Frontiers in Oncology, 2021)
Breast cancer is the most common malignancy occurring during gestation and should be managed with the same protocols as for young non-pregnant women. In early-stage breast cancer during pregnancy (PrBC), breast-conserving surgery (BCS) with delayed RT is a rational alternative to mastectomy. Regrettably, no specific guidelines on the surgical management of these PrBC are available. In this study, we investigated the feasibility and safety of BCS during the first trimester of pregnancy in women with early-stage PrBC. All patients with a diagnosis of PrBC during the first trimester of pregnancy jointly managed in two PrBC-specialized Centers were included in this study. All patients underwent BCS followed by adjuvant radiotherapy to the ipsilateral breast after delivery. Histopathological features and biomarkers were first profiled on pre-surgical biopsies. The primary outcome was the isolated local recurrence (ILR). Among 168 PrBC patients, 67 (39.9%) were diagnosed during the first trimester of gestation. Of these, 30 patients (age range, 23-43 years; median=36 years; gestational age, 2-12 weeks; median=7 weeks; median follow-up time=6.5 years) met the inclusion criteria. The patients that were subjected to radical surgery (n=14) served as controls. None of the patients experienced perioperative surgical complications. No ILR were observed within three months (n=30), 1 year (n=27), and 5 years (n=18) after surgery. Among the study group, 4 (12.3%) patients experienced ILR or new carcinomas after 6-13 years, the same number (n=4) had metastatic dissemination after 3-7 years. These patients are still alive and disease-free after 14-17 years of follow-up. The rate of recurrences and metastasis in the controls were not significantly different. The findings provide evidence that BCS in the first trimester PrBC is feasible and reasonably safe for both the mother and the baby.